Pushing past the human in Latin American cinema - Fornoff, Carolyn; Heffes, Gisela, 1971- (SUNY series in Latin American cinema., 2021)
"Sheds light on emergent Latin America cinema that addresses the politics of environmental destruction, the uneveness of climate change consequences, and new ways of visualizing the world beyond the human"--